The Vacuolar Protein Sorting-38 Subunit of the Arabidopsis Phosphatidylinositol-3-Kinase Complex Plays Critical Roles in Autophagy, Endosome Sorting, and Gravitropism - Liu, Fen; Hu, Weiming; Vierstra, Richard D. (Frontiers in Plant Science, 2018)
The family of phosphatidylinositols (PtdIns) plays essential roles in membrane identity and intracellular trafficking events. In animals and yeast, PtdIn-3-phosphate, which is particularly important for endosomal sorting, lysosomal/vacuolar transport and autophagy, is assembled by two conserved kinase complexes comprised of the catalytic VACUOLAR PROTEIN SORTING (VPS)-34 subunit, along with VPS15, AUTOPHAGY-RELATED (ATG)-6, and either ATG14 (complex I) or VPS38 (complex II). Here, we describe the Arabidopsis ortholog of VPS38 and show by interaction assays that it assembles into a tetrameric PtdIn-3 kinase complex II. Plants missing VPS38 are viable but have dampened pollen germination and heightened seed abortion, and display a dwarf rosette phenotype, with defects in leaf and vascular development and sucrose sensing. vps38 seeds accumulate irregular protein storage vesicles and suppress processing of storage proteins into their mature forms. Consistent with a role for PtdIn-3-phosphate in autophagy, vps38 mutants are hypersensitive to nitrogen and fixed-carbon starvation and show reduced autophagic transport of cargo into vacuoles. vps38 seedlings also have dampened root gravitropism, which is underpinned by aberrant vectoral auxin transport likely caused by defects in plasma membrane/endosome cycling of the PIN-FORMED family of auxin transporters necessary for asymmetric cell elongation. Collectively, this study places VPS38 and its class-III PtdIn-3 kinase complex at the nexus of numerous endosomal trafficking events important to plant growth and development.